The Effect of Employer Branding on Employees Retention, the Mediating role of Psychological Contract (An Empirical Study on the Employees of International Organizations in Syria) - اسماعيل, حسان (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The purpose of this study is to examine the effect of employer branding values and practices on the employees’ retention. Data were collected from both primary and secondary sources. A total number of 371 valid questionnaires were collected from international organizations located in Syria. The main results are: (1) Economic, interest, and developmental values have significant and positive effect on employees’ retention; (2) social value is significant and negative for employees’ retention; (3) and application value is insignificant. (4) Economic, interest, and developmental values are significant and positive for psychological contract; (5) social and application values are insignificant. (6) Psychological contract is positive and significant for retention. (7) Psychological contract fully mediates the relationship between employer branding (economic, interest, and developmental values) and employees’ retention, while it doesn’t play such role for social and application values. Recommendations and practical implications are mentioned at the end of the study.